Spheroid Culture of Mesenchymal Stem Cells - Zoe Cesarz; Kenichi Tamama (Hindawi Limited, 2016)
Compared with traditional 2D adherent cell culture, 3D spheroidal cell aggregates, or spheroids, are regarded as more physiological, and this technique has been exploited in the field of oncology, stem cell biology, and tissue engineering. Mesenchymal stem cells (MSCs) cultured in spheroids have enhanced anti-inflammatory, angiogenic, and tissue reparative/regenerative effects with improved cell survival after transplantation. Cytoskeletal reorganization and drastic changes in cell morphology in MSC spheroids indicate a major difference in mechanophysical properties compared with 2D culture. Enhanced multidifferentiation potential, upregulated expression of pluripotency marker genes, and delayed replicative senescence indicate enhanced stemness in MSC spheroids. Furthermore, spheroid formation causes drastic changes in the gene expression profile of MSC in microarray analyses. In spite of these significant changes, underlying molecular mechanisms and signaling pathways triggering and sustaining these changes are largely unknown.